2021
DOI: 10.1002/mrm.28879
|View full text |Cite
|
Sign up to set email alerts
|

A split‐label design for simultaneous measurements of perfusion in distant slices by pulsed arterial spin labeling

Abstract: Purpose Multislice arterial spin labeling (ASL) MRI acquisitions are currently challenging in skeletal muscle because of long transit times, translating into low‐perfusion SNR in distal slices when large spatial coverage is required. However, fiber type and oxidative capacity vary along the length of healthy muscles, calling for multislice acquisitions in clinical studies. We propose a new variant of flow alternating inversion recovery (FAIR) that generates sufficient ASL signal to monitor exercise‐induced per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 36 publications
(83 reference statements)
0
8
0
Order By: Relevance
“…These merits make ASL suitable not only for routine brain perfusion examination but also for perfusion studies in other body parts [ 12 , 13 , 14 , 16 , 17 , 18 , 21 , 22 , 23 , 33 ]. Although many studies have been published in the musculoskeletal field, those studies have focused mainly on exercise and peripheral arterial disease [ 26 , 34 , 35 , 36 ]. Recently, a study investigating musculoskeletal tumors found that ASL was able to diagnose malignant tumors efficiently and effectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These merits make ASL suitable not only for routine brain perfusion examination but also for perfusion studies in other body parts [ 12 , 13 , 14 , 16 , 17 , 18 , 21 , 22 , 23 , 33 ]. Although many studies have been published in the musculoskeletal field, those studies have focused mainly on exercise and peripheral arterial disease [ 26 , 34 , 35 , 36 ]. Recently, a study investigating musculoskeletal tumors found that ASL was able to diagnose malignant tumors efficiently and effectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The lower flow velocity may result in delayed enhancement in lesions at the extremities, and a PLD of 1500–2000 ms may not be optimal for perfusion study of the extremities. One previous study used a split-label design to improve measurements of muscle perfusion due to the long transit times in the extremities [ 26 ]. However, the influence of different PLDs in ASL perfusion imaging of musculoskeletal tumors has not been fully clarified Therefore, this study aimed to evaluate changes in the ASL-derived perfusion in different PLDs and to assess the performance of ASL in differentiating musculoskeletal tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The split‐label pulsed FAIR ASL scan, based on Baligand et al, 13 was used to assess muscle perfusion. The labeling scheme consisted of presaturation of the imaging slice, followed by either a slice‐selective or nonselective frequency offset‐corrected inversion (FOCI) 16 pulse of 15‐ms duration, after which postsaturation of the imaging slice was applied.…”
Section: Methodsmentioning
confidence: 99%
“…However, this technique limits the gap between the slices, thereby limiting muscle coverage. In previous work, we have overcome this limitation by adapting the FAIR 12 sequence in such a way that the label is also created in between two slices separated by a relatively large distance 13 . This new split‐label FAIR method enables the assessment of perfusion in two widely separated slices without the need for additional corrections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation